2017
DOI: 10.3389/fonc.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Stage IIIA Non-Small Cell Lung Cancer

Abstract: According to the eighth edition of the tumor–node–metastasis classification, stage III non-small cell lung cancer is subdivided into stages IIIA, IIIB, and IIIC. They represent a heterogeneous group of bronchogenic carcinomas with locoregional involvement by extension of the primary tumor and/or ipsilateral or contralateral lymph node involvement. Surgical indications have not been definitely established but, in general, long-term survival is only obtained in those patients in whom a complete resection is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The resectability of T4 or N2 disease is highly dependent on the local expertise of the surgeon and the management of complications by the comprehensive care team. 7 Moreover, despite an increased association between toxicity and combined chemoradiotherapy (CRT) in stage IIIA disease, previous studies have shown an advantage for combination CRT. 8 This survival advantage may be attributed to better management of the complications or toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…The resectability of T4 or N2 disease is highly dependent on the local expertise of the surgeon and the management of complications by the comprehensive care team. 7 Moreover, despite an increased association between toxicity and combined chemoradiotherapy (CRT) in stage IIIA disease, previous studies have shown an advantage for combination CRT. 8 This survival advantage may be attributed to better management of the complications or toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas large tumours without mediastinal lymph node involvement are usually resected, if possible, the possible role of surgery in the management of patients with stage IIIA disease with mediastinal involvement (T1-3N2M0) is the topic of considerable debate [5,67]. Randomised controlled trials have generally found no significant difference in overall survival when surgery was compared with radiotherapy/ chemoradiotherapy for stage IIIA-N2 disease.…”
Section: Surgerymentioning
confidence: 99%
“…Patients with pathologically proven N2–3 mediastinal lymph node metastases are usually recommended to undergo first line chemoradiation instead of surgery since no survival benefit has been demonstrated by additional surgery [ 4 ]. When mediastinoscopy demonstrates potentially resectable N2 metastases several treatment strategies can be followed: induction chemotherapy followed by surgery, induction chemoradiotherapy followed by surgery or definitive chemoradiotherapy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To strengthen these figures, recent survival data from the ASTER trial demonstrated equal 5-yr survival rates of 35% in both randomization groups, despite significantly different detection rates of upfront N2 disease [ 15 ]. Therefore, surgical treatment of minimal unforeseen N2 disease instead of definite chemoradiation is increasingly considered as treatment option as well [ 5 , 6 ]. In addition, the revised European Society of Thoracic Surgery (ESTS) guideline of mediastinal staging states that there is room for trials evaluating surgical treatment instead of chemoradiation for minimal N2 disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%